IMPACT OF OPERATIONAL RISK ON BANK CAPITAL ADEQUACY: EUROPEAN EVIDENCE - Bonachera López, Luis (My University, 2020)
The purpose of this thesis is to study the effect of European banks’ operational risk on their capital adequacy. Thesis distinguishes between observed data published by the European Banking Authority and adverse economic conditions compiled in their Stress tests. Thesis utilizes a panel dataset of 666 operational losses reported from 21 European countries between years 2013 and 2018 with a series of explanatory variables to control for events in the economy and financial indicators. Countries are grouped into regions of the European Union to control for different characteristics in the European banking system. Additional tests use econometric techniques and tests for changes in the qualitative insights during the time period chosen. Results conclude that there is not a significant relationship between the level of operational losses and the capital adequacy reported by European banks; heterogeneity of results is also evident among different regions within European banking system. Rather than external risks to bank’s operations, financial indicators such as solvency and liquidity play an important role in the final capital adequacy ratio reported by European banks. Similarly, operational risk is not found to be driving lower capital adequacy ratio under financial distress or worst-case economic conditions. By employing robustness tests and alternative models, these findings are reinforced. Additionally, other risks such as market and credit have more potential to determine capital adequacy systemic shock.
Keywords: risks; financial crimes; banking sector; Capital Adequacy; systemic risk; operational risk; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance